Analysis of Student Satisfaction in Axioo Class Program Towards LMS UPMYSKILL using Technology Acceptance Model (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
In the context of e-learning development, this study attempts to determine the factors that influence student satisfaction with UpMySkill Learning Management System (LMS). Furthermore, this study explores the problems faced by students in the Axioo Class Program (ACP) and builds a hypothesis that perceived usefulness (PU) and ease of use (PEOU) have an impact on behavioural intention (BU), attitude towards use (ATU), and actual use (AU). Slovin and purposive sampling methods were used to select 313 students in total, and data collection took place between December 20 and 27, 2024. Cronbach's Alpha was used to assess the reliability and validity of the instruments. PLS-SEM analysis revealed that PEOU had a positive effect on PU, while PU had a substantial effect on ATU (β = 0.700; p < 0.001) and AU. 55% of the variation in BU and 47.3% of the variation in student satisfaction can be explained by this model. Improving interactive features, providing real-time technical assistance, and streamlining the LMS design are some suggestions to improve the quality of UpMySkill